2010
DOI: 10.1016/j.lfs.2010.05.019
|View full text |Cite
|
Sign up to set email alerts
|

cis-4-decenoic acid provokes mitochondrial bioenergetic dysfunction in rat brain

Abstract: It is therefore presumed that impairment of mitochondrial homeostasis provoked by cis-4-decenoic acid may be involved in the brain dysfunction observed in medium-chain acyl-CoA dehydrogenase deficient patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It is postulated that clinical symptoms, including CNS complications such as convulsion, coma and lethargy, may be triggered by the accumulation of metabolites and their acyl-CoA derivatives that disrupt intermediary metabolism [6669]. The hydrolysis of the acyl-CoA derivatives and subsequent accumulation of free organic acids can lead to severe acidosis that can be life threatening [3].…”
Section: Neuroprotection Afforded By L-carnitine Supplementation In Pmentioning
confidence: 99%
“…It is postulated that clinical symptoms, including CNS complications such as convulsion, coma and lethargy, may be triggered by the accumulation of metabolites and their acyl-CoA derivatives that disrupt intermediary metabolism [6669]. The hydrolysis of the acyl-CoA derivatives and subsequent accumulation of free organic acids can lead to severe acidosis that can be life threatening [3].…”
Section: Neuroprotection Afforded By L-carnitine Supplementation In Pmentioning
confidence: 99%
“…Table 4 shows that medium-chain fatty acids accumulating in MCAD deficiency deregulate various crucial mitochondrial functions in brain, liver and skeletal muscle. It can be observed in the table that the medium-chain fatty acids inhibit energy production, utilization and transfer [ 102 106 ], uncouple OXPHOS [ 107 109 ] and induce oxidative stress [ 106 , 110 , 111 ], which may result at least partly from the blockage of the respiratory chain stimulating superoxide and other ROS production. The deleterious effects were more pronounced with decanoic acid and cis -4-decenoic acid, that also induced mPT, a condition that compromise all mitochondrial functions, including energy production, maintenance of cellular redox status and Ca 2+ retention capacity, culminating in cell death [ 112 ].…”
Section: Toxicity Of the Major Metabolites Accumulating In Faodmentioning
confidence: 99%
“…It is presumed that this pathomechanism possibly contribute to the chronic and neurologic symptoms seen in these defects. Moreover, although it is difficult to evaluate the relative contribution of the toxic fatty acids in the neuropathology of these diseases, it is conceivable that there may be a synergistic action between the toxicity of these Metabolic inhibition 54,55 Decrease of NAD(P)H content 54,55 Respiratory chain and creatine kinase activities inhibition 54,[56][57][58] Induction of oxidative stress 52,53 Decrease of Ca 2þ retention capacity 56 Induction of permeability transition 56 metabolites, hyperammonemia, and hypoketotic hypoglycemia (energy deficit) leading to brain damage. It is expected that the development of new drugs targeting the mitochondrion, initially in animal models and thereafter as adjuvant therapeutic approaches for the patients, may become an important focus in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MCFA, particularly decanoic and cis-4-decenoic acids, behave as uncouplers of OXPHOS and metabolic inhibitors, as well as inductors of mitochondrial permeability transition and oxidative stress. [51][52][53][54][55][56] These effects may be associated at least partly with the blockage of the respiratory chain provoked by MCFA that may stimulate superoxide and other ROS production 54,[56][57][58] and with the protonophoric action of these fatty acids due to the transbilayer movement of undissociated (linked to protons) fatty acids through the mitochondrial inner membrane toward the mitochondrial matrix. 59,60 Mitochondrial dysfunction has also been suggested as an important pathomechanism involved in the neurological symptoms that affect individuals with LCHAD deficiency since there are clear human evidences of mitochondrial damage in these patients.…”
Section: Evidence That Mitochondrial Dysfunction Is Caused By the Majmentioning
confidence: 99%